2014
DOI: 10.2478/cipms-2014-0016
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of chromium, nickel, iron and manganese content in wheat, flour, bran and selected baked products

Abstract: Considering the nutritional values, breadstuff plays a big part in covering human nourishment needs and constitutes a base of all day diet. Moreover, bread is an excellent source of numerous vitamins and minerals the abundance of which depends on the degree of grinding. Thus, it seems to be very important to know the composition and level of bio-elements. That is why the main target of this study was to evaluate the concentration of selected trace elements: chromium (Cr), nickel (Ni), iron (Fe) and manganese (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 2 publications
3
3
0
Order By: Relevance
“…Manganese is an essential dietary mineral which is a component of a number of metalloenzymes involved in amino acid, lipid and carbohydrate metabolism. Nuts, dried fruits and chocolate are the main dietary sources of manganese; cereal‐based products also contribute to its intake mainly due to the levels found in wheat grain (25 mg/kg, Bawiec et al., ). A decrease of up to approximately 6% is observed in the GM maize as compared to the non‐GM comparator.…”
Section: Assessmentsupporting
confidence: 84%
“…Manganese is an essential dietary mineral which is a component of a number of metalloenzymes involved in amino acid, lipid and carbohydrate metabolism. Nuts, dried fruits and chocolate are the main dietary sources of manganese; cereal‐based products also contribute to its intake mainly due to the levels found in wheat grain (25 mg/kg, Bawiec et al., ). A decrease of up to approximately 6% is observed in the GM maize as compared to the non‐GM comparator.…”
Section: Assessmentsupporting
confidence: 84%
“…Variation in Ni concentration between bread types could be an influence of equipment which was used during the bread making process. A similar observation was reported by (Bawiec et al, 2014). Furthermore, it may be due to used water and soil type of grown wheat (Ofori et al, 2016).…”
Section: Nickelsupporting
confidence: 85%
“…The high variation of Cr in studied bread samples may be due to use of metals during the baking process. But, the variation of Cr concentration may be due to type of used flour, environment and soil type of wheat grain grown and used water for preparation of bread yeast (Bawiec et al, 2014).…”
Section: Chromiummentioning
confidence: 99%
“…(2013), while Bawiec et al . (2014) reported an increase from 0.09 to 0.31 mg kg −1 with the decrease of wheat flour refining degree. Levels of Ni of 0.02 mg kg −1 were reported by Plustea et al .…”
Section: Resultsmentioning
confidence: 99%
“…Ni has recently become the object of attention by the European Food Safety Agency (EFSA), which has raised its tolerable daily intake (TDI) from 2.8 to 13 lg kg À1 of body weight (Schrenk et al, 2020). In wheat flour, levels of Ni from 0.08 to 0.09 mg kg À1 were observed by Tejera et al (2013), while Bawiec et al (2014) reported an increase from 0.09 to 0.31 mg kg À1 with the decrease of wheat flour refining degree. Levels of Ni of 0.02 mg kg À1 were reported by Plustea et al (2022) in LF.…”
Section: International Journal Of Food Science and Technology 2023mentioning
confidence: 99%